The Attitudes, Perceptions and Concerns of Pedestrians and Vulnerable Road Users to Shared Space: A Case Study from the UK - Charles Musselwhite (Journal of Urban Design, 2013)
The concept of shared space is increasingly being incorporated into urban areas in the UK, promoting a major change in the way streets are designed. Shared space is a design feature that aims to encourage pedestrians, cyclists and drivers to share the same deregulated space. However, there is a lack of evidence underpinning shared space, in terms of attitudes and usability, particularly for vulnerable road users including blind and partially sighted, elderly and wheelchair users. This research used street accessibility audits and focus groups with vulnerable pedestrians and 100 completed on-street questionnaires to investigate attitudes and behaviour towards a shared space scheme in Hereford, UK. The findings have shown that despite being very positive towards the scheme, particularly in terms of aesthetics, pedestrians and vulnerable road users had a number of issues and concerns with the design and usability of Widemarsh Street, in particular with nuances of design including the kerbs and vehicular access to the street.